2011
DOI: 10.1002/cne.22687
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic and immunohistochemical organization of the human habenular complex

Abstract: The habenular complex (HbCpx) is a phylogenetically conserved brain structure located in the epithalamus of vertebrates. Despite its fundamental role in decision-making processes and the proposed link between habenular dysfunction and neuropsychiatric conditions, little is known about the structural and functional organization of the HbCpx in humans. The goal of this study was thus to provide a first systematic morphologic and immunohistochemical analysis of the human HbCpx to begin dissecting its nuclear and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
50
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 83 publications
(126 reference statements)
2
50
0
Order By: Relevance
“…Histology of post-mortem human brain shows partition of Hb into medial and lateral parts, connected by the Hb commissure, similarly to the partition observed in rodents (23). Another morphologic and immunohistochemical analysis showed that, overall, the MHb subnuclear organization in humans is similar to that observed in rodents, whereas the shape, relative size, and intranuclear organization of the LHb show significant difference (24). One important difference resides in the substantially enlarged dorsal part of the human LHb that shows GABA-B receptors immunoreactive cells.…”
Section: Anatomymentioning
confidence: 52%
See 1 more Smart Citation
“…Histology of post-mortem human brain shows partition of Hb into medial and lateral parts, connected by the Hb commissure, similarly to the partition observed in rodents (23). Another morphologic and immunohistochemical analysis showed that, overall, the MHb subnuclear organization in humans is similar to that observed in rodents, whereas the shape, relative size, and intranuclear organization of the LHb show significant difference (24). One important difference resides in the substantially enlarged dorsal part of the human LHb that shows GABA-B receptors immunoreactive cells.…”
Section: Anatomymentioning
confidence: 52%
“…One important difference resides in the substantially enlarged dorsal part of the human LHb that shows GABA-B receptors immunoreactive cells. This growth in size possibly indicates increased influence of limbic and striatal afferents into the LHb of humans compared to rodents (24). …”
Section: Anatomymentioning
confidence: 99%
“…The Hb is a small brain structure in the posterior thalamus that is divided into MHb and LHb components that are functionally different (Andres et al 1999; Díaz et al 2011). Because of its location, we carefully selected MHb and LHb seed regions, and it is generally precarious to investigate the function of such a small subcortical structure.…”
Section: Hb Rsfc In Healthy Control Subjectsmentioning
confidence: 99%
“…For example, healthy subjects exhibited functional connections between the LHb and frontal brain areas (M1/S1, S2, FP, and dlPFC), subcortical regions (thalamus, CPu, NAc, and hippocampus), and brainstem structures (PAG, VTA, and SNc). The LHb receives inputs from numerous brain regions such as the lateral hypothalamus, basal ganglia, NAc, and frontal brain regions; its main outputs go to the PAG, VTA, and SNc (Andres et al 1999;Bianco and Wilson 2009;Díaz et al 2011), which are predominantly nuclei that regulate dopaminergic and serotonergic systems (Aizawa et al 2012). Additionally, we found functional connections between the Hb and the PAG, a region involved in a number of processes including pain modulation (Behbehani 1995;Linnman et al 2012), as well to the RVM, which is known to send excitatory and inhibitory fibers to dorsal horn spinal cord neurons and is thus actively involved in pain modulation (Fields et al 1995).…”
Section: Hb Rsfc In Healthy Control Subjectsmentioning
confidence: 99%
See 1 more Smart Citation